2001
DOI: 10.1179/135100001101536409
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced peroxynitrite production in human platelet-rich plasma

Abstract: Recent data support the possible role of nitric oxide (NO*) in the development of insulin signalling. The aim of this study was to examine the effect of insulin on NO* production by platelets. The chemiluminescence of platelet-rich plasma prepared from the blood of healthy volunteers was measured in the presence of luminol. Indirect detection of NO* by luminol is possible in the form of peroxynitrite produced in the reaction of NO* with a superoxide free radical. Luminol oxidation induced by hydroxyl free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Kashiwagi et al (12) indirectly showed that insulin treatment increases superoxide in rats. Their findings also supported the hypothesis of Facchini et al (25), in which age-associated oxidative stress is determined by hyperinsulinemia, and the findings of Wittman et al (26), in which human platelets generate peroxynitrites under insulin stimulation.…”
Section: Discussionsupporting
confidence: 80%
“…Kashiwagi et al (12) indirectly showed that insulin treatment increases superoxide in rats. Their findings also supported the hypothesis of Facchini et al (25), in which age-associated oxidative stress is determined by hyperinsulinemia, and the findings of Wittman et al (26), in which human platelets generate peroxynitrites under insulin stimulation.…”
Section: Discussionsupporting
confidence: 80%
“…Wittmann et al [16] reported that incubation of platelet-rich plasma with insulin induces an increase of peroxynitrite formation, due to the reaction between NO and superoxide anion. In platelets, peroxynitrite inhibits cyclooxygenase via nitration of tyrosine residues, resulting in inhibition of thromboxane generation [17••]; thus, the insulin-induced increase of peroxynitrite could play a role in the insulin-induced reduction of platelet aggregation.…”
Section: The Role Of Insulin and Insulin Resistance In The Modulationmentioning
confidence: 98%